Sampling - Sharon L. Lohr
Sharon L. Lohr's SAMPLING: DESIGN AND ANALYSIS provides a modern introduction to the field of sampling. With a multitude of applications from a variety of disciplines, the book concentrates on the statistical aspects of taking and analyzing a sample. Overall, the book gives guidance on how to tell when a sample is valid or not, and how to design and analyze many different forms of sample surveys